Screening of process parameters for the production of bioprotein from EFB by Aspergillus Terreus UniMAP AA-1 for fish feeds application - Mohamad Firdaus Ismail (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Nowadays, agro-waste biomass have become the new grossing trends in bioconversion research including in bioprotien production due to increasing of demands and the conventional protein which require higher cost of production could be potentially replaced by protein. The palm oil's empty fruit bunch (EFB) had been selected as the raw material in this research . The nutritional value and cheaper carbon source of its composition had become an interest for futher study in the bioprotien production through solid state fermentation (SSF). Aspergillus terreus is the filamentous fungus had been chosen due its ability to produce cellulose enzyme which to degrade cellulose content of the EFB.